Move structures and the use of hedges and boosters in the discussion sections of tourism and pharmacology research articles - Nur Zafirah Razali (2023)
The ability of authors to alternate interpretations and cautiously analyse data is associated with effective academic writing, and a research article’s (RA) acceptance or rejection is contingent on the way the Discussion section of the research article is written. The current study utilises Yang and Allison’s (2003) model, along with Hyland’s (1998a) and Hinkel’s (2005) taxonomies, to investigate how authors in Tourism and Pharmacology organise discussions in the respective research articles. The study employs move analysis to examine the use of hedges and boosters in discussing research results. In this regard, the current study employed a mixed method through an exploratory sequential research design, particularly by using content analysis and quantitative analysis to analyse the data in the Discussion sections of 20 Tourism and 20 Pharmacology research articles in terms of the number of sentences employing the moves outlined in Yang and Allison’s (2003), the frequencies of hedges and boosters found in the corpora, and the percentages of both datasets. Interviews were also conducted with specialist informants from Tourism and Pharmacology fields to supplement the data obtained in the study. The findings indicated that both Tourism and Pharmacology authors reported and commented on research results interrelatedly; however, a major difference was observed in terms of how the results were commented on such that Pharmacology authors were more likely to compare research results with the literature compared to their Tourism counterparts. Besides, the findings also revealed that both Tourism and Pharmacology authors utilised more hedges than boosters when discussing research results to avoid overclaiming the results and maintain a degree of certainty or uncertainty. The findings of this study offer valuable insights for future academic authors and students, helping them develop strategies for proficiently discussing research results and employing appropriate hedging and boosting devices in academic writing, particularly in the context of research articles (RAs).